Pengaruh Modal Usaha, Luas Usaha Dan Profesionalisme Sumber Daya Manusia Terhadap Pendapatan Toko Kebutuhan Primer Pasar Pekalongan Lampung Timur - Fera Laras Hati; Yulita Zanaria; Ana Septiani (Universitas Muhammadiyah Metro, 2023)
This study aims to determine the effect of business capital, business size and professionalism of human resources on the income of primary needs stores in Pekalongan market, East Lampung. Data obtained from observations and questionnaires. The population of this study were shops in Pekalongan Market, East Lampung, namely 50 samples of shops consisting of 20 large shops and 30 small shops. The analysis technique used is multiple linear regression analysis. The results of the analysis are then analyzed with the classical assumption test and the F test. The results of this study indicate that business capital, business area and human resource professionalism have a significant effect on the income of primary needs stores in Pekalongan market, East Lampung.